PENERAPAN REGRESI LOGISTIK MULTINOMIAL PADA PEMILIHAN ALAT KONTRASEPSI WANITA (Studi Kasus di Desa Tonggara Kecamatan Kedungbanteng Kabupaten Tegal) - Sulistio, Erna; Ispriyanti, Dwi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2010)
The development of a growing population, causing many problems within national development, so the program necessary to reduce the population of family planning program, one of the programs is Contraceptive Services. A variety of contraceptive choices provided by the government especially for women, including: pill, injection, IUD, implant, tissue KB, tubectomy, cream, jelly, and foam. The selection of contraceptives for women have to weigh various factors. So we want to know the factors which influence women in choosing a particular contraceptive. By testing the significance of the multinomial logistic regression model through the G test statistic can be shown there are four factors that influence contraceptive use, namely maternal age, number of living children, age of last child, and pregnancy plans. Keywords: Contraception, Multinomial Logistic Regression